Faktor Penyebab Pernikahan Dini Di Kota Gorontalo - Syahrul Ramadhan Ayuba; Nirwan Junus; Melisa Towadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Early marriage is a marriage carried out by someone who is a teenager or under the age determined by the Marriage Law No. 1 of 1974 which explains the age at which a person can enter into marriage, namely 19 year old men and 16 year old women. The purpose of this study is to find out about early marriage, the factors that cause early marriage, the impact of early marriage, and the community's view of early marriage. To find out the overall and more in-depth problems, in this study a qualitative approach was used which is useful for providing data and facts about early marriage and its problems in the City of Gorontalo. Then the data is analyzed systematically so as to obtain in-depth answers about early marriage and its problems in the City of Gorontalo. From the results of this study it was found that the factors that cause early marriage are different from the past. The main factors behind early marriage in Gorontalo City are promiscuity among adolescents which causes adultery, economic factors, education, arranged marriages, and social factors. Early marriage has an impact on psychology, social, economy, health and education. Community views differ on early marriage, namely positive and negative depending on the impact and factors behind early marriage.